A novel weak fuzzy solution for fuzzy linear system - Salahshour, Soheil; Ahmadian, Ali; Ismail, Fudziah; Baleanu, Dumitru (MDPI, 2016)
This article proposes a novel weak fuzzy solution for the fuzzy linear system. As a matter of fact, we define the right-hand side column of the fuzzy linear system as a piecewise fuzzy function to overcome the related shortcoming, which exists in the previous findings. The strong point of this proposal is that the weak fuzzy solution is always a fuzzy number vector. Two complex and non-complex linear systems under uncertainty are tested to validate the effectiveness and correctness of the presented method.